Translation of Bacteriophage Qβ RNA by Cytoplasmic Extracts of Mammalian Cells - Morrison, Trudy G. (National Academy of Sciences, 1973)
Cytoplasmic extracts from Krebs II mouse ascites cells and from L cells translate messenger RNA from coliphage Qβ with fidelity to produce products that migrate on polyacrylamide gels with those products directed by Qβ RNA in an Escherichia coli cell-free system. The mammalian cell extracts correctly initiate and terminate Qβ coat protein synthesis, as shown by: (i) [(3)H]lysine-and [(3)H]arginine-labeled tryptic peptides derived from the coat-sized product resemble these from authentic Qβ coat protein, (ii) Qβ coat (which contains methionine only at the N-terminal end) can be radioactively labeled with methionine only if the methionine is formylated, and (iii) L cell extracts directed by Qβ am(-)11 (an amber mutant in the coat protein) RNA make no completed coat-sized material, but do make a peptide the size of the authentic amber coat fragment.